SOCIALIZATION OF FIRE PREVENTION AND CONTROL IN SRIGONCO VILLAGE, MALANG - Rahmania, Nima Eka Nur; Kuncoro, Achmat; Robbani, Adhar Rouhul Ni’am (Community Service Journal of Indonesia, 2023)
The causes of fires are not only natural factors but also human factors, especially negligence and unpreparedness in protecting against fire. This community service is carried out because fires often occur in residential areas. Socialization on fire prevention and control measures in Srigonco Village, Malang is a form of education and practice which aims to provide an understanding of the factors that cause fires, how to prevent and control them so that it is hoped that participants can prevent fires from occurring and extinguish fires using modern or traditional fire extinguishers. The activity was held on August 24th, 2023 at the Srigonco Malang Village Hall. The targets are health cadres, UKK cadres and rescue teams. Before carrying out the activity, 2 month preparation process was carried out, starting from selecting materials to submitting permits to the relevant parties. The results of the evaluation of activities attended by 24 participants showed that participants participated in the activities enthusiastically and conducively, and the activities were carried out smoothly and on time. There was an increase in participants' knowledge from an average score of 60 to 95. Most participants can also use traditional (APT) and modern fire extinguishers (APAR).